Determination of synthetic drugs as adulterant in herbal anti-diabetic medicines by HPLC - Chowdhury, Anika Tasnim (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.